Fertility preservation in the pediatric population—experience from a German Cryobank for ovarian tissue - Baston-Büst, Dunja M.; Bielfeld, Alexandra P. (Frontiers in Endocrinology, 2022)
Counselling children on the possibility of fertility preservation prior to a gonadotoxic treatment supports the decision making process, taking into account that the patients are in a very vulnerable and mentally exhausting situation following the diagnosis. Referral to specialists can be optimized on site by routing slips with contact addresses, phone numbers and mail contacts, available time slots for consultation, possibly offers for cost coverage and an easy to understand information leaflet about the different options available. Taking into account that some of the options for fertility preservation in the pre pubertal population especially are still experimental, the unique possibility of fertility preservation, before the beginning of gonadotoxic therapeutic schemes, which may cause premature ovarian insufficiency or azoospermia in the future, should be highlighted.